A feasible method for independently evaluating the mechanical properties of glial LC and RGC axons by combining atomic force microscopy measurement with image segmentation. (February 2022) - Liu, Liu; Liu, Yushu; Li, Tan; Li, Lin; Qian, Xiuqing; Liu, Zhicheng
Abstract: Purpose: The deformation of lamina cribrosa (LC) under the elevated intraocular pressure (IOP) might squeeze the retinal ganglion cell (RGC) axons and impair the visual function. Mechanical behaviors of LC and RGC axons are supposed to be related to the optic nerve damage of glaucoma patients. However, they cannot be independently studied with the existing methods because the LC and RGC axons intertwine in the LC area. This study proposed a feasible method to evaluate the respective mechanical properties of glial LC and RGC axons of rats. Methods: The atomic force microscope (AFM) nano-indentation experiment was performed on unfixed cryosection samples acquired from the glial LC tissues of eight eyes from four rats. For each sample, three regions of interests (ROIs) with sizes of 20 × 20 μm 2 were selected from the ventral, central and dorsal regions of the sample, respectively, and the nano-indentation was performed on 128 × 128 points within each ROI to obtain a Young's modulus image. The glial LC and RGC axons were segmented on each modulus images using Otsu thresholding segmentation method, and their respective Young's modulus was further extracted for statistical analysis. Results: Young's modulus of glial LC and RGC axons are 297 ± 98 kPa and 76 ± 36 kPa in ventral regions, 342 ± 84 kPa and 84 ± 32 kPa in central regions, 280 ± 104 kPa and 75 ± 30 kPa in dorsal regions, respectively. No significant differences are found among the Young's modulus of different regions, both for glial LC and RGC axons. Conclusions: This study takes the nature property of the LC area as a composite material into consideration, and proposes a feasible method to distinguish between the glial LC and RGC axons and measure their respective Young's modulus. These findings may provide useful information for establishing finite element models of the optic nerve head and promote the study on the deformation of the optic nerve under high intraocular pressure, and finally contribute to the early diagnosis of glaucoma. Graphical abstract: Image 1 Highlights: A method to assess mechanical properties of rat glial lamina cribrosa and retinal ganglion cell axons is proposed. Rat glial LC area is a typical two-phase composite material. There is no significant regional difference in the Young's modulus of the glial LC area. The proposed method promotes the study on early diagnosis of glaucoma. The proposed method could also be used for other two-phase composite soft tissues.